Impact of Education on Knowledge and Perception of Antenatal Care Among Primigravida Mothers, Residing in Farasan, Kingdom of Saudi Arabia: A Community-based Interventional Study - Santhi Muttipoll Dharmarajlu; Hawazen Ibrahim Musawa; Khwlah Mohamed Qradi; Jawaher Yahya Gradi; Awatif Mrwaei Mohssin; Hanein Hussain Hakami (International Journal of Women's Health Nursing And Practices, 2023)
Pregnancy is one of the most cherished phases in the life of a woman. This timeframe holds immense importance for both the mother and the infant. Offering appropriate prenatal care during pregnancy is crucial for the health of the mother and the growth of the foetus. It provides a chance to promote sound parenting techniques and healthful conduct. The quality of prenatal care contributes to sustaining overall well-being throughout an individual's lifetime. On the other hand, insufficient care during pregnancy disrupts the care cycle and impacts the well-being of both women and babies. The aim of this study was to assess the knowledge and perception of antenatal care among primigravida mothers residing in Farasan, Saudi Arabia. Through quantitative survey approach and pre-experimental – one group pre- and post-test design, the 50 primigravida mothers were selected by purposive sampling method. A structured interview schedule was employed to evaluate the awareness and knowledge of antenatal care among first-time pregnant mothers. Their perceptions about antenatal care were assessed using a 5-point Likert scale. To educate them about antenatal care, instructional material was provided through video presentations. The study's findings revealed that, in terms of awareness, the mean score for the pre-test was 7.18 ± 1.924, whereas for the post-test it was 22.76 ± 1.188, resulting in a mean difference of 15.58. This suggests that the first-time pregnant mothers had significantly improved knowledge about antenatal care following the educational programme, indicating the effectiveness of the teaching approach. In perception the overall mean score during pre-test was 21.58 ± 3.214 and in post-test the overall mean score obtained by mothers was 57 ± 1.841, with a mean difference of 35.42. It reveals that the primigravida mothers had highly favourable attitude towards antenatal care after implementation of educational programme. The 't' values calculated for the awareness and perception scores were 9.88 and 6.49, respectively, at the 0.05 significance level. Consequently, it is evident that there was a significant enhancement in the knowledge and attitude of first-time pregnant mothers regarding antenatal care following the implementation of the educational programme. These results can be valuable in devising a health intervention Program with the objective of enhancing maternal healthcare practices and, in turn, advancing the overall health of women.
Keywords: Knowledge; antenatal care; educational programme; perception; primigravida mothers